KARAKTERISTIK FISIK, KIMIA DAN ORGANOLEPTIK VEGETABLE LEATHER CABAI HIJAU (Capsicum annuum var. annuum) DENGAN PENAMBAHAN BERBAGAI KONSENTRASI PEKTIN - Permatasari, Putri Devi; Parnanto, Nur Her Riyadi; Ishartani, Dwi (Universitas Sebelas Maret (UNS), 2017)
Vegetable leather is a thin sheet-shaped product made of vegetables (puree) are processed by drying method. Green chilli contains high vitamin C, low calories value 23 cal/100 gr and contain fibers which is quite high as 1.3 g/100 g. In this study, pectin hydrocolloid was added to improve less plastic texture in vegetable leather. The purpose of this research is to identify the influence of the variation concentration of pectin against physical characteristics (tensile strength), chemical (water activity, moisture content, ash contain, vitamin C, fiber and calories value) and organoleptic (colour, flavour, taste, texture, and overall) vegetable leather green chilies as well as knowing the best concentration of pectin that based on physical, chemical and organoleptic characteristics of vegetable leather green chilies. Experimental design used in this research was Completely Randomized Design (CRD) based upon one factor which was the effects of pectin concentration addition. Research data were analyzed by one way ANOVA method and continued using DMRT analysis on the significance level α = 0.05, if there were significant differences between the means. The result showed that variations in the concentration of pectin have significant effect on water activity, moisture content, ash contain, and fiber. However, the variations of pectin concentration does not affect the value of tensile strength, vitamin C and calories value. Based on the analysis of physical, chemical, and organoleptic shows the vegetable leather green chili with the addition of 0.3% pectin is the best formula. Vegetable leather green chilies with 0.3% pectin concentration has tensile strength 4.6866 N, water activity 0.55, moisture content (wb) 14.959%, ash contain (db) 19.209%, food fiber (db) 15.795%, calories value 3.015,551 cal/g.